2008
DOI: 10.1038/sj.bjc.6604769
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the prognostic and predictive value of HER family mRNA expression in high-risk early breast cancer: A Hellenic Cooperative Oncology Group (HeCOG) study

Abstract: The aim of the study was to evaluate the prognostic ability of the transcriptional profiling of the HER family genes in early breast cancer, as well as to investigate the predictive value of HER2 mRNA expression for adjuvant treatment with paclitaxel. RNA was extracted from 268 formalin-fixed paraffin-embedded (FFPE) tumour tissue samples of high-risk breast cancer patients enrolled in the randomised HE10/97 trial, evaluating the effect of dose-dense anthracycline-based sequential adjuvant chemotherapy with or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
40
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 48 publications
7
40
2
Order By: Relevance
“…In line with these findings, HER-3 gene amplification has been associated with a reduced disease-free survival and shorter relapse-free survival rates (Bieche et al, 2003;Sassen et al, 2008). However, at least other three studies have reported opposite findings, with better outcomes associated with a positive HER-3 expression (Pawlowski et al, 2000;Lee et al, 2007;Koutras et al, 2008). One potential explanation for the discrepant findings regarding the prognostic value of HER-3 expression levels may be that clinical outcomes can also be influenced by its phosphorylation level or the expression of HER-3 ligands (Koutras et al, 2010).…”
Section: Discussionsupporting
confidence: 61%
“…In line with these findings, HER-3 gene amplification has been associated with a reduced disease-free survival and shorter relapse-free survival rates (Bieche et al, 2003;Sassen et al, 2008). However, at least other three studies have reported opposite findings, with better outcomes associated with a positive HER-3 expression (Pawlowski et al, 2000;Lee et al, 2007;Koutras et al, 2008). One potential explanation for the discrepant findings regarding the prognostic value of HER-3 expression levels may be that clinical outcomes can also be influenced by its phosphorylation level or the expression of HER-3 ligands (Koutras et al, 2010).…”
Section: Discussionsupporting
confidence: 61%
“…Immunohistochemical analysis is a valid method as it shows protein expression. However, the clinical introduction of immunohistochemical assessment for predicting sensitivity to chemotherapeutic agents is still problematic due to difficulties in quantitative measurement (inter-observer variations in interpretation) and the lack of calibrated quantification techniques (27)(28)(29). in addition, only 10-20% of patients with PDAC are candidates for curative resection (3).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other ErbB family members, ErbB4 may have tumor-suppressor activities because ErbB4 decreases breast epithelial cell proliferation (Pitfield et al, 2006;Muraoka-Cook et al, 2006a;Feng et al, 2007), and promotes differentiation (Muraoka-Cook et al, 2006b and apoptosis (Naresh et al, 2006;Vidal et al, 2007). Consistently, many studies suggest that the ErbB4 expression correlates with a good prognosis in breast cancer (Kew et al, 2000;Witton et al, 2003;Barnes et al, 2005;Koutras et al, 2008). However, inconsistent results have also been frequently reported (Tang et al, 1999;Junttila et al, 2005;Maatta et al, 2006;Zhu et al, 2006).…”
Section: Introductionmentioning
confidence: 98%